2006
DOI: 10.1007/s00296-005-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and management of fetuses at risk for, or affected by, congenital heart block associated with autoantibodies to SSA (Ro), SSB (La), or an HsEg5-like autoantigen

Abstract: The congenital heart block (CHB), diagnosed in structurally normal hearts, is strongly associated with, if not caused by, maternal SSA/SSB antibodies (Abs). It develops between 16 and 24 weeks' gestation, coincidentally with the increased transplacental IgG passage, and a window of unique cardiac vulnerability. Less is known about rare CHB cases in which neither cardiac malformations nor SSA/SSB Abs are detectable. We report on four pregnant women: patient 1 at high CHB risk (owing to Sjögren's syndrome (SS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
2
24
0
1
Order By: Relevance
“…We have again shown that most mothers who have a pregnancy complicated by significant fetal cardiac involvement are not identified before the pregnancy because they do not a have connective tissue disease and thus are not referred for prospective fetal evaluation. Consequently, to improve the yield of early detection before CAVB, we agree with a previous suggestion that a successful program to prevent severe cardiac complications would require the screening for anti-Ro antibodies of all pregnant women irrespective of their symptoms or clinical status (33).…”
Section: Discussionsupporting
confidence: 61%
“…We have again shown that most mothers who have a pregnancy complicated by significant fetal cardiac involvement are not identified before the pregnancy because they do not a have connective tissue disease and thus are not referred for prospective fetal evaluation. Consequently, to improve the yield of early detection before CAVB, we agree with a previous suggestion that a successful program to prevent severe cardiac complications would require the screening for anti-Ro antibodies of all pregnant women irrespective of their symptoms or clinical status (33).…”
Section: Discussionsupporting
confidence: 61%
“…These autoantibodies damage the AV conduction tissue possibly by inflammation or direct ion channel interaction in the early stage and later by fibrosis [3-5]. The prognosis of isolated congenital heart block in patients presenting as fetuses or at birth is associated with higher morbidity and mortality rates (which may be as high as 30-50%) [6].…”
Section: Discussionmentioning
confidence: 99%
“…As most mothers of neonates with NLE do not have any connective tissue disease, a previous suggestion that all pregnant women should be screened for anti-Ro antibodies irrespective of their symptoms or clinical status may be considered reasonable [138]. …”
Section: Anti-ro Antibodies and Autoimmune Diseasesmentioning
confidence: 99%